Digital transformation adoption and its influence on performance: an empirical study of creative companies in Vietnam - Tran, Van Hai Trieu; Pavelková, Drahomíra (Creativity Studies, 2024)
The purpose of the study clarifies the digital transformation adoption and how it impacts on the performance of creative companies in Vietnam. This investigation applied the technology–organization–environment framework and the structural equation modeling approach. The data was collected from 674 survey participants who are middle and senior managers or owners of creative companies in Vietnam, mainly located in Hanoi and Ho Chi Minh City. The structural equation modeling analysis indicates a positive relationship between technological, organizational, and environmental factors, and digital transformation adoption; the digital transformation adoption positively affects a company performance. These findings substantially contribute to the knowledge of digital technologies, digital transformation, company performance, and creative industries in the context of technology, organization, and environment. This research also provides insights for policymakers, readers, scientific communities, and management levels of creative industries to understand more about the environment of Vietnam’s creative industries.